Níveis dietéticos de proteína degradada no rúmen para novilhas de corte suplementadas a pasto durante o verão - Dresch, Alan (2021)
The ideal level of metabolizable protein allows satisfactory productivity gains and reduces losses of nitrogen compounds and their release into the environment. The purpose of this study was to evaluate the effect of a 75% increase in the dietary content of rumen degradable protein (RDP) on performance, intake and diet digestibility of heifers receiving energy protein supplement in the rainy season. Forty Nellore heifers, 12±2 months of age and mean body weight of 210±27.8kg were used. The experimental design was completely randomized with two levels of protein supplementation: rumen degradable protein in order to meet 100% of requirements (PDR100) and rumen degradable protein so that the requirement was exceeded by 75% (PDR175). Forage availability and growth, height of entry and exit of animals from paddocks, intake and digestibility, ruminal ammonia nitrogen, urea nitrogen in urine, serum urea nitrogen and performance were evaluated. Crude protein consumption was higher for animals treated with PDR175. The opposite behavior was observed for starch consumption, where PDR100 presented higher consumption. The amount and availability of forage, plus the concentrate feed provided to the animals in the PDR100 treatment was enough to meet the nutritional requirements of the animals for the intended weight gain. The levels of degradable protein in the rumen did not influence the rumen pH, however, it was found that the pH was higher when collected in the morning. Ruminal ammonia nitrogen (RAN) was influenced by RDP levels and collection periods. For urine urea nitrogen (NUU), PDR175 was higher than PDR100. For serum urea nitrogen (NUS), there was no difference between PDR levels, however, an interaction between treatments and periods was observed for NUS. The 75% increase in PDR requirements did not improve performance. The supply of 175% of the RDP requirements in the supplementation of beef cattle in the rainy season does not improve the performance of beef heifers in tropical pasture in the rainy season.